Rare Leiomyoma of the Tunica Dartos: A Case Report with Clinical Relevance for Malignant Transformation and HLRCC - Robert C. Bell; Evan T. Austin; Stacy J. Arnold; Frank C. Lin; Jonathan R. Walker; Brandon T. Larsen (Case Reports in Pathology)
Background. Genital leiomyomas fall under the broader category of cutaneous leiomyomas, which are rare smooth muscle neoplasms accounting for 5% of all leiomyomas. Genital leiomyomas arising from the dartos muscle are exceedingly rare with fewer than 30 cases reported in the literature. They are typically benign and adequately treated with simple surgical excision; however, previously reported cases of malignant transformation and a possible link to the hereditary leiomyomatosis and renal cell cancer (HLRCC) syndrome warrant closer follow-up. Case Presentation. We report a case of a 47-year-old male refugee from Rwanda found to have a mobile, pea-sized, mildly painful scrotal lesion near the left penoscrotal junction and 1.5 cm indeterminate vascular mass in the right kidney. Surgical excision of the scrotal nodule was performed and the diagnosis of a dartoic leiomyoma was rendered. The presence of moderate nuclear atypia, rare mitotic activity, and close surgical margins prompted a wide reexcision. We report the surgical approach, pathologic findings, and clinical follow-up related to this scrotal lesion. Conclusion. Scrotal leiomyomas demonstrate a high rate of recurrence and pose a risk for malignant transformation. They may also indicate an underlying autosomal dominant syndrome associated with increased risk for development of an aggressive form of renal cell carcinoma. When discovered, management should include surgical excision, screening for syndromic features, and routine follow-up.